The Polypeptide Subunit Structure of the DNA-dependent RNA Polymerase of Zea mays Chloroplasts - Smith, H. J. (1974)
Analysis of the maize chloroplast DNA-dependent RNA polymerase by electrophoresis on polyacrylamide gels that contain sodium dodecyl sulfate shows that the enzyme is multimeric. It contains at least two polypeptides of 180,000 and 140,000 daltons. Polypeptides of lower molecular mass that are associated with the enzyme at several stages of purification may also be subunits of the enzyme. Electrophoresis of a mixture of purified maize nuclear DNA-dependent RNA polymerase IIA and chloroplast polymerase on sodium dodecyl sulfate-polyacrylamide gels resolves the 160,000 dalton polypeptide of IIA from the 140,000 dalton polypeptide of the chloroplast enzyme, but does not resolve the 180,000 dalton components found in both enzymes. The polypeptides of less than 40,000 daltons in the highly purified maize nuclear IIA preparations are absent from preparations of purified maize chloroplast RNA polymerase.